Studies in Mineral Nutrition of Indian Forest Species. III. Effect of Deficiency of Macro-nutrients on Net Assimilation Rate and Water Content of Salmalia malabarica Schott. and Endl. under Varying Light Conditions - Nanda, K. K. (Indian Forester, 1965)
Fifty-five d.y old seedling. of Salmalia malcharica were transferred under three light cOllditions- Long Day (LD); Normal Day (ND) and light of low intensity (LI) - and were divided into eight lots each. One lot received solution deficient in all major elements. The second lot received solution complete in all nutrients and served as control. Of the remaining six lots each received nutrient solution deficient in one of the macro-elementsN-, P, K, Ca, Mg, or S respectively. Periodic. I samples were taken for fresh and dry weight determinations. From the data of fresh and dry weights calculations were made of the water content of different plant parts and the net assimilation rates at different stages in the growth of the plant. But for per hour of illumination it is slightly higher in ND plants compared to L.D. plants probably due to low intensity of light used to supplement the normal day. The net assimilation ratc is the highest in plants receiving complete nutrient solution and the lowest in those deficient for all macro-elements. It is slightly higher in those deficient for N, P and K but fairly high in p lants deficient for Ca, mg and S during the earlier stages. Top/root dry weight ratio remains higher in LD than ND plants throughout the period of growth. The ratio decreases with Macro-nutrient deficiencies. The decrease is more marked in plants deficient for N than in those d eficient for P and K. In plants deficient for Ca, Mg and S the ratio is bigher than the control as their deficiency results in greater reduction in the dry weight of the root than shoot. The accumulation of dry m atter in the root is more after the growth of the top slows down. The water content of root, stem, petiole and leaf is higher in LD than in ND plants during the earlier stages. Later on, however, it becomes higher in the latter. The water content of roct, stem and petiole shows a fall after 87 days in plants deficient for N, P and K. In the control and in plants deficient for Ca, Mg and S the water content increases and the fall is delayed to 118 days. The water content of leaf does not differ with the nutrient treatments. It ;s considered that the deficiency of either regulatory substance(s) or nutrients limits the production of nucleic acids, as a consequence of which the meristematic activity of the growing apex is arrested. This causes a change in the balance of demand and consequently an alteration in the distribution of metabolites and accumulation of dry matter in different parts of the plant and the mistake of water. The ecological significance of these findings and their application in forestry is discussed.